EFEKTIVITAS LAYANAN KONSELING KARIR INDIVIDU DENGAN PENDEKATAN TRAIT AND FACTOR UNTUK MENINGKATKAN ORIENTASI BERKARIR PADA REMAJA DI DESA JAYA BAKTI, KECAMATAN MADANG SUKU I, KABUPATEN OKU TIMUR - Aziez Alfariedzi Pangiestu; Wikan Galuh Widyarto (Jurnal At-Taujih, 2022)
This study aims to determine the level of understanding of youth career orientation in Jaya Bakti Village, Madang Tribe I, Kab. East Oku and to determine the effectiveness of individual career counseling services with a trait and factor approach in improving understanding of career orientation. This research is a pre-experimental research with the One Group Pretest Posttest Design model. The population is 36 teenagers, while the research sample is 2 teenagers with a very low average score based on purpose sampling technique and pretest results. The instrument of data collection was using a purpose sampling Likert scale. The data analysis technique used the homogeneity test, while the data analysis requirements used the SPSS hypothesis test. The results of the research that have been known that the average condition of adolescents who lack understanding of career orientation in Jaya bakti Village, Madang Suku, Kab. East Oku got an average score of 133.89 which was in the medium category. The results of the paired sample test show the difference between the pretest and posttest scores. From the results of the calculation of the paired sample test, a significant 2-tailed value of 0.000 was obtained. Based on the applicable provisions, it is known that the paired sample test Sig 2-tailed test results are 0.000 <0.05, which means Ha is accepted and Ho is rejected.The conclusion results of the paired sample test, it can be concluded that there is an increase in adolescent career orientation for pretest and posttest through individual counseling services using the trait and factor approach.